2017
DOI: 10.1038/s41467-017-00977-8
|View full text |Cite
|
Sign up to set email alerts
|

Actomyosin polarisation through PLC-PKC triggers symmetry breaking of the mouse embryo

Abstract: Establishment of cell polarity in the mammalian embryo is fundamental for the first cell fate decision that sets aside progenitor cells for both the new organism and the placenta. Yet the sequence of events and molecular mechanism that trigger this process remain unknown. Here, we show that de novo polarisation of the mouse embryo occurs in two distinct phases at the 8-cell stage. In the first phase, an apical actomyosin network is formed. This is a pre-requisite for the second phase, in which the Par complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(129 citation statements)
references
References 69 publications
(64 reference statements)
7
89
1
Order By: Relevance
“…The PKCλ/ι belongs to the atypical group of PKCs, which consists of another isoform PKCζ. The aPKC isoforms have been implicated in cell lineage patterning in preimplantation embryos (Zhu, Leung, Shahbazi, & Zernicka-Goetz, 2017). We demonstrated that both PKCζ and PKCλ/ι regulate self-renewal vs. differentiation potential in both mouse and rat embryonic stem cells (Dutta et al, 2011;Mahato et al, 2014;Rajendran et al, 2013).…”
Section: Introductionmentioning
confidence: 71%
“…The PKCλ/ι belongs to the atypical group of PKCs, which consists of another isoform PKCζ. The aPKC isoforms have been implicated in cell lineage patterning in preimplantation embryos (Zhu, Leung, Shahbazi, & Zernicka-Goetz, 2017). We demonstrated that both PKCζ and PKCλ/ι regulate self-renewal vs. differentiation potential in both mouse and rat embryonic stem cells (Dutta et al, 2011;Mahato et al, 2014;Rajendran et al, 2013).…”
Section: Introductionmentioning
confidence: 71%
“…Polarisation at the 8-cell stage is the first event generating asymmetries within blastomeres from a structural point of view (Ducibella et al, 1977;Louvet et al, 1996;Vinot et al, 2005;Ziomek and Johnson, 1980). Recent work has advanced our understanding of the signalling pathways involved in the polarisation process (Zhu et al, 2017). The actomyosin contractility machinery is recruited to cell contact-free membrane in a chain of events initiated by phospholipase C (PLC).…”
Section: Discussionmentioning
confidence: 99%
“…To test this, we used Ro-31-8220 (RO), a PKC inhibitor that leads to reduced phosphorylation of ERM proteins (pERM), a marker of the apical domain (Liu et al, 2013). Reduced apical pERM in turn leads to a decrease in apical F-actin (Liu et al, 2013), which further impairs the establishment of polarity as the actomyosin network is required for the apical localisation of the Par complex (Zhu et al, 2017). We found that embryos treated with inhibitor from the 2-to the 8-cell stage not only exhibited reduced proportion of apical to basolateral pERM (A/B pERM ratio) but were also unable to form apical actin rings ( figure 5A and 5D) consistent with disruption of apicobasal polarity.…”
Section: N/c Yap Ratio Increase From the 2-to 8-cell Stage Is Dependementioning
confidence: 99%
“…The asymmetric localization of the Par/aPKC complex has been used as an indicator of apical-basal cell polarity in a set of animals, including bilaterians 4,5,14,15,53,56-59,63,66,68,69,76-80 and a cnidaria 5,21 . While in the studied bilaterians this asymmetry is established and maintained since the earliest stages of development 60,63,65,71,88,89 , in the cnidarian N. vectensis there is no early asymmetrical localization of any of the Par components 5,21 and embryonic polarity is controlled by the Wnt signaling system 16,73,[90][91][92] . In spite of these differences, once epithelial tissues form and true-epithelial cell-polarity is established in both bilaterian and cnidarian species, the asymmetric localization of Par proteins become highly polarized and is maintained through development.…”
Section: Par Protein Asymmetry Is Established Early But Not Maintainementioning
confidence: 99%
“…This mechanism is deployed in metazoan cells to establish embryonic and epithelial cell polarity during early development and is critical for axial organization 5,15,17,21,22,36,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] . In most bilaterian cells, symmetry breaking is mediated by the Par system set up maternally during the earliest cleavage stages 5,60,70,71 .…”
Section: Introductionmentioning
confidence: 99%